2021
DOI: 10.1016/j.ultsonch.2021.105661
|View full text |Cite
|
Sign up to set email alerts
|

Process intensification and kinetic studies of ultrasound-assisted extraction of flavonoids from peanut shells

Abstract: Highlights Flavonoids was extracted from peanut shells using an ultrasound-assisted process. Ultrasound used as intensification tool with highest flavonoids yield of 9.263 mg/g. UAE gave higher yield as compared with that of SE and HRE. Phenomenological model was fitted for kinetic modelling and it’s validation. Comparison of two models have been introduced to describe the extraction kinetic of flavonoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 59 publications
4
20
0
Order By: Relevance
“…The extraction kinetics for TA from PSPs with WF‐UAE were investigated based on Peleg's model. This model provided a well explanation of the process of solid–liquid extraction and was evident in previous literature such as studying extraction kinetics of thymol concentration from plectranthus amboinicus leaves using UAE (Zahari et al, 2020), punicalagin from pomegranate peel by ultrasound (Rakshit et al, 2020), pectin extraction by way of ultrasound‐assisted extraction with acid from melon peel (Raji & Kiani, 2020), and in our previous research on flavonoids extraction from peanut shells (Liao et al, 2021). The equation of this model first proposed by Peleg in 1988 was used in the present study and shown as follows:Ctgoodbreak=C0goodbreak+t/)(k1goodbreak+k2twhere C t represents the concentration of TA at t (mg/g), t represents the extraction time (min), C 0 represents the initial concentration of TA at t = 0 (mg/g), k 1 and k 2 represent Peleg's rate constant (min g/mg) and capacity constant (g/mg), respectively.…”
Section: Methodsmentioning
confidence: 71%
“…The extraction kinetics for TA from PSPs with WF‐UAE were investigated based on Peleg's model. This model provided a well explanation of the process of solid–liquid extraction and was evident in previous literature such as studying extraction kinetics of thymol concentration from plectranthus amboinicus leaves using UAE (Zahari et al, 2020), punicalagin from pomegranate peel by ultrasound (Rakshit et al, 2020), pectin extraction by way of ultrasound‐assisted extraction with acid from melon peel (Raji & Kiani, 2020), and in our previous research on flavonoids extraction from peanut shells (Liao et al, 2021). The equation of this model first proposed by Peleg in 1988 was used in the present study and shown as follows:Ctgoodbreak=C0goodbreak+t/)(k1goodbreak+k2twhere C t represents the concentration of TA at t (mg/g), t represents the extraction time (min), C 0 represents the initial concentration of TA at t = 0 (mg/g), k 1 and k 2 represent Peleg's rate constant (min g/mg) and capacity constant (g/mg), respectively.…”
Section: Methodsmentioning
confidence: 71%
“…1 E , the extraction yield of TPC and TMA showed the same change trend, which increased gradually before 35 min, then decreased slightly with the increase in extraction time. Liao et al [50] also found that too long extraction time will reduce the extraction yield of flavonoids from peanut shells.This can be ascribed to the fact that phenols are easy to oxidized and hydrolyzed for a long time. Another possible reason is that the TPC and TMA from the inner section of particles of purple eggplant peels diffuse through the pores, which has a certain inhibitory effect on the extraction rate [51] .…”
Section: Resultsmentioning
confidence: 99%
“…The traditional extraction methods of flavonoids include heat reflux extraction (HRE) [10], alkali extraction [11], ultrasound-assisted extraction [12,13], microwave-assisted extraction [14] and supercritical fluid extraction [15,16], etc. The processes of extracting flavonoids from sea buckthorn leaves mainly includes solvent extraction [17,18], ultrasonicassisted extraction [19,20], microwave-assisted extraction [21], enzyme-assisted extraction [22] and synergistic extraction [23].…”
Section: Introductionmentioning
confidence: 99%